Laser ice scaffolds modeling for tissue engineering - Meglinski, I. V.; Varejka, M.; Woodman, Anthony C.; Turner, Anthony P. F.; Piletsky, Sergey A. (John Wiley & Sons, Ltd, 2005)
Tissue engineering is one of the most exciting and rapidly growing areas in biomedical engineering that offers vast potential for changing traditional approaches to meeting many pharmaceutics and critical health care needs. Currently the bottle-neck area in this multidisciplinary field appears to be materials and fabrication technology for the design of artificial extracellular matrices/scaffolds that support culturing and growth of new tissue. We have shown that stable relief structures can be created and maintained in the bulk of ice by continuous s canning with computer-guided IR CO2 laser. The optimal laser beam intensity and fluence rate distribution within the ice sample, as well as the rate of scanning were estimated based on the Monte Carlo model utilized physical/optical properties of ice. The results of numerical simulation are agreed well with the observed experimental results of thermo-coupling measurements and obtained microscopic images.